Factors associated with older adults’ cognitive decline 6 months after gamma-variant SARS-CoV-2 infection - Peixoto, Vanessa Giffoni M. N. P.; Facci, Lucas Alves; Barbalho, Thiago C. S.; Souza, Raíssa Nascimento; Duarte, Alice Mendes; dos Santos, Marina Bruxel; Almondes, Katie Moraes (Frontiers in Neurology, 2024)
Background: Cognitive deficits are commonly reported after COVID-19 recovery, but little is known in the older population. This study aims to investigate possible cognitive damage in older adults six months after contracting COVID-19, as well as individual risk factors. Methods: This cross-sectional study involved 70 participants aged 60 to 78 with COVID-19 six months prior and 153 healthy controls. Montreal Cognitive Assessment -Basic (MoCA-B) screened for cognitive impairment; Geriatric Depression Scale and Geriatric Anxiety Inventory screened for depression and anxiety. Data were collected on demographics and self-reports of comorbid conditions. Results: The mean age of participants was 66,97±4,64 years. A higher proportion of individuals in the COVID group complained about cognitive deficits (X2=3.574; p=0.029) and presented with deficient MoCA-B scores (X2=6.098, p=0.014) compared to controls. After controlling for multiple variables, all the following factors resulted in greater odds of a deficient MoCA-B: COVID-19 6-months prior (OR, 2.44; p=0.018), age (OR, 1.15; p<0.001), lower income (OR, 0.36; p=0.070), and overweight (OR, 2.83; p=0.013). Further analysis pointed to individual characteristics in COVID-19-affected patients that could explain the severity of the cognitive decline: age (p=0.015), lower income (p<0.001), anxiety (p=0.049), ageusia (p=0.054), overweight (p<0.001), and absence of cognitively stimulating activities (p=0.062). Conclusion: Our study highlights a profile of cognitive risk aggravation over aging after COVID-19 infection, which is likely mitigated by wealth but worsened in the presence of overweight. Ageusia, anxiety, being overweight, and absence of routine intellectual activities are risk factors for more prominent cognitive decline among those infected by COVID-19.